Exercise Attenuates Anabolic Steroids-Induced Anxiety via Hippocampal NPY and MC4 Receptor in Rats - Joksimovic, Jovana; Selakovic, Dragica; Jovicic, Nemanja; Mitrovic, Slobodanka; Mihailovic, Vladimir; Katanic, Jelena; Milovanovic, Dragan; Rosic, Gvozden (Frontiers in Neuroscience, 2019)
The aim of our study was to evaluate the effects of chronic administration of nandrolone-decanoate (ND) or testosterone-enanthate (TE) in supraphysiological doses and a prolonged swimming protocol, alone and in combination with ND or TE, on anxiety-like behavior in rats. We investigated the immunohistochemical alterations of the hippocampal neuropeptide Y (NPY) and melanocortin 4 receptor (MC4R) neurons, as a possible underlying mechanism in a modulation of anxiety-like behavior in rats. Both applied anabolic androgenic steroids (AASs) induced anxiogenic effect accompanied with decreased serum and hippocampal NPY. The exercise-induced anxiolytic effect was associated with increased hippocampal NPY expression. ND and TE increased the number of MC4R, while the swimming protocol was followed by the reduction of MC4R in the CA1 region of the hippocampus. However, NPY/MC4R ratio in hippocampus was lowered by AASs and elevated by exercise in all hippocampal regions. An augmentation of this ratio strongly and positively correlated to increased time in open arms of elevated plus maze, in the context that indicates anxiolytic effect. Our findings support the conclusion that alterations in both hippocampal NPY and MC4R expression are involved in anxiety level changes in rats, while their quantitative relationship (NPY/MC4R ratio) is even more valuable in the estimation of anxiety regulation than individual alterations for both NPY and MC4R expression in the hippocampus.